Inklusion und die Rechte junger Menschen Eine rechtskreisübergreifende Aufgabe. - Scheiwe, Kirsten; Schröer, Wolfgang; Wapler, Friederike; Wrase, Michael (Schriften zum Familien- und Sozialrecht, 2023)
The reform of the Child and Youth Welfare Law in 2021 has initiated far-reaching changes towards human rights-oriented, non-discriminatory participation and inclusive child and youth welfare. The coordination of child and youth welfare law (SGB VIII) and of disability rights (SGB IX) for all young people in a structured system with different benefit laws and seven competent agencies is a great challenge and a task for the future, which will be discussed from a legal, socio-educational and sociological perspective, taking into account the practice. With contributions by Prof. Dr. Albrecht Rohrmann, Prof. i.R. Dr. Kirsten Scheiwe, Prof. Dr. Wolfgang Schröer, Dr. Eric Van Santen, Prof. Dr. Arne von Boetticher, Prof. Dr. Friederike Wapler, Anke Welke, Prof. Dr. Felix Welti and Prof. Dr. Michael Wrase.